2trax3: raising accessibility and everyday use of automatic motion analysis in (combat) sports via ml enhanced 2D to 3D estimation algorithms - Duvelek, S.; Hoelbling, D.; Baranyi, R.; Breiteneder, R.; Pinter, K.; Grechenig, T. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
A sound technique forms the fundamental basis for many sports, particularly Martial Arts, as it often distinguishes between successful hits and being hit. However, the process of improving one`s technique is highly intricate, often requiring expert feedback and expensive technology such as 3D motion capturing. The integration of automated technique analysis has the potential to streamline this process and make it more accessible. In this study, the aim is to democratize technique analysis by developing and evaluating a web application. This application allows users to upload 2D video recordings of themselves performing the double side kick technique and receive immediate feedback. To validate the analysis generated by the application, it was compared to a Vicon motion app 3D analysis of the same data from a preliminary study involving 44 participants. The results of Bland-Altman plot analysis demonstrated a highly significant agreement between the 3D and 2D performance indicato rs (Mean differences: relative phase duration: <0.04s; vector spreading angle: <15 degrees; relative body position <13%), indicating that the web application is a suitable tool for fast and effective motion analysis.